Lipopolysaccharide Stimulates Peripheral Blood Lymphocytes of Patients with Rheumatoid Arthritis to Produce IL-10 in vitro - Israa M. Subhi (World Journal of Experimental Biosciences, 2023)
Lipopolysaccharide (LPS) plays an important role in stimulating the pro-inflammatory immune response, especially in patients with rheumatoid arthritis (RA). Production of IL-10 in the host plays an important role in reducing the effect of the pro-inflammatory immune response. The role of LPS of Pseudomonas aeruginosa in stimulating IL-10 in patients with RA is not clear in the literature. The current study aims to determine the ability of the lymphocytes of patients with RA to produce IL-10 after being stimulated with LPS of P. aeruginosa in vitro. The human peripheral blood lymphocytes (PBLs) were isolated from patients with RA (test group A) and healthy cohorts (HC) (test group B), and they were cultured in vitro and stimulated with 1 µg of LPS of P. aeruginosa and PBS. The folds of the IL-10 gene expression of IL-10 were estimated in the PBLs, while the concentration of IL-10 was measured in the cell culture supernatants. The results of the folds of the gene expression and the concentrations of Il-10 of test groups were compared with control groups [PBLs of patients with RA (control groups A) and HC (control groups B) stimulated with PBS]. The significant elevations of IL-10 gene expression and IL-10 concentrations were seen in the PBLs cultures of test group A as compared with control groups A and B. The results showed no significant difference in the IL-10 gene expression and IL-10 concentrations of cell culture of test group B as compared with control groups A and B. It can be concluded that the LPS stimulates the lymphocytes of patients with RA to produce IL-10 and help in balance of the effect of pro-inflammatory immune reaction.
Keywords: Interleukin-10, Lipopolysaccharide, Peripheral blood lymphocytes, Tissue culture.